Stereotype of State’s Mother and the Hidden-Career: a Study on the Roles and Perception of Wives of Presidents and Vice Presidents Candidates in the 2014 Election - Gadis Arivia (Yayasan Jurnal Perempuan, 2014)
This paper investigates stereotype of first ladies and image being built during 2014 Indonesia presidential election. Wives of candidates in the election are highly accomplished as well as being graduated from universities, yet these facts are not exposed adequately in the media as part of public education on equality. Most of the time, they are being posited as faithful-partner and bold-supporter of their husbands/ partners. Interviews held by the media frequently narrate the drama within the house, family, and their romance. Their career and professionalism are being hidden from the public. Platform of empowerment and gender equality are highly cultivated, promoted, and campained by political-parties as well as NGOs, yet missed the wives to be involved. The capacity of the presidential candidate’s wives on gender, equality and women’s empowerment platforms designed by the political parties need to be promoted and scrutinized.